NDSP 12: Atherogenic index of plasma as a useful marker of cardiovascular disease risk among Pakistani individuals; a study from the second National Diabetes Survey of Pakistan (NDSP) 2016-2017 - Asher Fawwad; Yasir Mahmood; Saima Askari; Anum Butt; Abdul Basit; Mujeeb Ur Rehman Abro; Khawaja Ishfaq Ahmed; Khurshid Ahmed; Sobia Sabir Ali; Ahmed Bilal; Anam Butt; Bikha Ram Devrajani; et al. (Elsevier, 2023)
Aim: To investigate the reliability of atherogenic index of plasma (AIP) as a marker of cardiovascular disease risk and its correlation with CVD risk factors. Methodology: It is a sub-study of the second National Diabetes Survey of Pakistan (NDSP) 2016-2017, an epidemiological survey including both genders with >20 years of age in all four provinces of Pakistan. Out of 213 clusters, twenty-seven clusters were selected and households were identified from each cluster. Selected members of every 10th household were counseled for a visit to the campsite after observing an overnight fast. Standardized techniques were used for measuring height, weight, BMI, waist circumference, and blood pressure. Biochemical parameters including oral glucose tolerance test, lipid profile, and various lipid-derived parameter/ratios were also analyzed via standardized methods. Results: A total of 7351 individuals were selected for this sub-analysis after fulfilling the inclusion criteria. Mean AIP score was calculated as 0.38 ± 0.31 with statistically significant difference among all groups (p < 0.0001), and according to the AIP risk categorization, a majority of 6996 individuals (95.2%) fell in the high-risk category of developing CVD, whereas 258 (3.5%) were in moderate and only 97 (1.3%) individuals were found in the low-risk category. Multiple logistic regression analyses showed male gender and diabetes as risk factors for developing CVD based on the AIP score. Furthermore, various lipid-derived parameters LDL-C and HDL-C, TG and HDL-C, lipoprotein combined index (LCI) were shown a strong correlation with AIP. Conclusion: The significant association between AIP and CVD risk factors exists and high levels of AIP in Pakistani population may be an alarming sign in developing cardiovascular disease.